The effects of a cognitive information processing career intervention on the dysfunctional career thoughts, locus of control, and career decision self-efficacy of underprepared college students - Henderson, Kristina M. (Kansas State University, 2009)
This study investigated the impact of a seven-session career intervention in a First Year Experience course on the dysfunctional career thoughts, locus of control, and career decision self-efficacy of underprepared college students. The career intervention was based on the cognitive information processing approach to career decision making (Peterson, Sampson, & Reardon, 1991; Peterson, Sampson, Reardon, & Lenz, 1996; Reardon, Lenz, Sampson, & Peterson, 2000; Sampson, Reardon, Peterson, & Lenz, 2004) and utilized the CTI workbook (Sampson, Peterson, Lenz, Reardon, & Saunders, 1996b). Participants in the study were full-time freshmen enrolled in remedial academic courses at a small, open-enrollment institution. The study was a Nonequivalent Control Group design with delayed posttest. Ten hypotheses were identified and tested. The Career Thoughts Inventory, the Rotter IE Scale, and the Career Decision Self-Efficacy-Short Form were administered at pretest, posttest, and delayed posttest. ANCOVA was used to analyze differences between the mean scores by group for each of the dependent variables. In addition, dependent t-tests were used to examine the differences between the mean scores within group for each of the dependent variables. Results of this study indicated that underprepared students who participated in the career intervention significantly improved dysfunctional career thoughts on all variables from pretest to posttest. Further, improvement in dysfunctional career thoughts was maintained four weeks after the intervention. Significant differences were also found at posttest between the treatment and control groups for CTI Total and Decision-Making Confusion. In addition, a significant positive correlation was found between dysfunctional career thinking and locus of control, indicating the participants with higher levels of dysfunctional career thoughts also had a more external locus of control. Locus of control was not significantly different from pretest to posttest in the treatment group; however, locus of control did become more internal following the intervention. At delayed posttest, locus of control of the treatment group was not significantly different from Rotter’s (1966) normative sample while the control group continued to be significantly more external than the normative sample. While career decision self-efficacy was not significantly different from pretest to posttest, students’ scores indicated confidence in their ability to perform career tasks.
Keywords: Dysfunctional career thoughts; Locus of control; Cognitive Information Processing; Career intervention; Career decision self-efficacy; Underprepared college students; Education, Higher (0745)